Playing Host Since 1948: Jordan's Refugee Policies and Faith-Based Charity. Issue 2 (3rd April 2022) - Gutkowski, Stacey
ABSTRACT: Since 1948, Jordan has hosted successive waves of refugees from neighboring states. Since the onset of a new refugee crisis in 2011, the evolution of Jordan's humanitarian assemblage has provided opportunities for the marked expansion, institutionalization, and globalization of Islamic and Christian humanitarianism within Jordan. The level of international influence the Jordanian government has allowed during the crisis has helped facilitate greater religious privacy for local Islamic and Christian charitable actors to express their religious vision through their charitable work with refugees. The regime has responded by allowing, surveilling, and sometimes seeking to reshape such religious effervescence in its own image. These dynamics cannot be understood purely through the history of refugee hosting in Jordan but also as ongoing competition between the regime and other actors, particularly Islamists affiliated to its main opposition Muslim Brotherhood, over dīn al-millah, or everyday religious expression.